Analyzing decision-making factors in the generational succession of rural youth. Issue 2 (December 2022) - Lago, Adriano; dos Santos Amorim, Gabrieli; Boscardin, Mariele; Zucatto, Luis Carlos; Spanevello, Rosani Marisa
Abstract: This paper analyzes the decision-making factors that influence the generational succession of young members or children of members of agricultural cooperatives in the grain, meat, and dairy segments in the southern region of Brazil. First, 25 factors that influence the process of generational succession, called decision-making factors, were identified through a literature review and dialogue with the cooperatives. Then, using the methodology adapted from Slack, Chambers and Johnston (2007), a sample of 308 young people between 18 and 30 years old evaluated the level of importance and performance of the decision-making factors indicated. In the respondents' opinion, none of the 25 factors performed better than their importance, as all factors present the possibility of improvement. However, according to the evaluation methodology used in this paper, 20 factors (property size; access to technologies; access to media and information; labor availability; diversification of agricultural activities; income provided by agricultural activities; access to education; social interaction and number of people in the community; professional expectations; remuneration received by the youth; education; type of work performed; marriage; autonomy; family dialogue; encouragement and recognition; technical assistance; presence of the cooperative, union, and associations; and access to marketing) performed adequately and did not require improvements in any of the three cooperatives. On the other hand, five factors need improvement: leisure infrastructure; road infrastructure; social valorization; rural credit and public policies; and price, according to the grain cooperative; leisure infrastructure, road infrastructure, social valorization; and price, according to the dairy cooperative; and social valorization and price, according to meat cooperative. We concluded that a significant part of the factors (80 %) performed in an adequate way directly or indirectly in the three cooperatives. The youth of the three cooperatives indicated social valorization and price among the factors that need improvement. Thus, we highlight that agricultural cooperatives should seek to understand their role in the face of decision-making factors that need improvement and seek to improve them. Highlights: The young successors are mostly single and male. Twenty-five decision-making factors were identified in the generational succession process. None of the 25 decision-making factors performed better than its importance attributed by young people. 80 % of the decision-making factors showed adequate performance. Investments in improvements in technical assistance can generate positive impacts on young people and on the relationship with the cooperative.